2019
DOI: 10.3389/fimmu.2019.02291
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Protective Role of Vitamin D Supplementation on HIV-1 Infection

Abstract: HIV infection remains a global and public health issue with the incidence increasing in some countries. Despite the fact that combination antiretroviral therapy (cART) has decreased mortality and increased the life expectancy of HIV-infected individuals, non-AIDS conditions, mainly those associated with a persistent inflammatory state, have emerged as important causes of morbidity, and mortality despite effective antiviral therapy. One of the most common comorbidities in HIV-1 patients is Vitamin D (VitD) insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 95 publications
5
60
0
1
Order By: Relevance
“…Data were collected prior to universal cART in pregnancy, which may have affected the mean CD4%. The present study echoes the favorable relation between vitamin D status and immune outcomes reported elsewhere [34,35].…”
Section: Plos Onesupporting
confidence: 91%
“…Data were collected prior to universal cART in pregnancy, which may have affected the mean CD4%. The present study echoes the favorable relation between vitamin D status and immune outcomes reported elsewhere [34,35].…”
Section: Plos Onesupporting
confidence: 91%
“…In 3 of 7 studies, CD4+ T cell count increased, but effect on viral load was inconclusive since most patients were on cART. [112] H9N2 influenza…”
Section: Clinical and Epidemiological Findings Regarding Covid-19mentioning
confidence: 99%
“…In particular, the paper reports that supplementation with a daily dose of vitamin D between 4000-7000 IU for at least 12 weeks can reduce the expression of CD38 and Ki67 in CD8+ T lymphocytes, inflammatory monocytes (CD14+ CD16+), as well as the expression of PD1 + (an exhaustion marker) in CD4+ T cells, with an increase in CD4+/CD8+ T cell ratio. This leads to the important assumption that brisk supplementation in vitamin D-deficient HIV-infected patients could help reduce chronic inflammation and comorbidities [16] that are still frequent among these patients despite the constant amelioration of combination antiretroviral therapy (cART) [17]. Human cathelicidin peptide LL37 also modulates the recognition of viral dsRNA by Toll-like receptor 3 (TLR 3).…”
Section: Immunomodulatory and Antiviral Role Of Vitamin Dmentioning
confidence: 99%